Fluidized bed combustion bottom ash: A better and alternative geo-material resource for construction - Mandal A.K.; Paramkusam B.R.; Sinha O.P. (My University, 2025)
Though the majority of research on fly ash has proved its worth as a construction material, the utility of bottom ash is yet questionable due to its generation during the pulverized combustion process. The bottom ash produced during the fluidized bed combustion (FBC) process is attracting more attention due to the novelty of coal combustion technology. But, to establish its suitability as construction material, it is necessary to characterize it thoroughly with respect to the geotechnical as well as mineralogical points of view. For fulfilling these objectives, the present study mainly aims at characterizing the FBC bottom ash and its comparison with pulverized coal combustion (PCC) bottom ash, collected from the same origin of coal. Suitability of FBC bottom ash as a dike filter material in contrast to PCC bottom ash in replacing traditional filter material such as sand was also studied. The suitability criteria for utilization of both bottom ash and river sand as filter material on pond ash as a base material were evaluated, and both river sand and FBC bottom ash were found to be satisfactory. The study shows that FBC bottom ash is a better geo-material than PCC bottom ash, and it could be highly recommended as an alternative suitable filter material for constructing ash dikes in place of conventional sand. © 2018, © The Author(s) 2018.